2003
DOI: 10.1177/07419325030240040301
|View full text |Cite
|
Sign up to set email alerts
|

The Educational Plight of Foster Children in Schools and What Can Be Done About It

Abstract: The purpose of this article is to increase awareness of teachers and other school personnel to the difficulties of many foster children. More specifically, we intend to alert them to the problems these youngsters have while they are in school and once they have left. Moreover, we intend to apprise educators of the fact that large numbers of foster children are receiving, or should be receiving, special services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 0 publications
0
45
0
Order By: Relevance
“…), poverty, backwardness, a sense of neglect, failure or rejection, or are part of a deviant delinquent environment (Emerson and Lovitt 2003;Heflinger et al 2000;Hussey and Guo 2005;Mitic and Rimer 2002;Rutter 2000;Schiff and Benbenishty 2006;Shin 2003;Vinnerljung et al 2005).…”
Section: Discussionmentioning
confidence: 98%
“…), poverty, backwardness, a sense of neglect, failure or rejection, or are part of a deviant delinquent environment (Emerson and Lovitt 2003;Heflinger et al 2000;Hussey and Guo 2005;Mitic and Rimer 2002;Rutter 2000;Schiff and Benbenishty 2006;Shin 2003;Vinnerljung et al 2005).…”
Section: Discussionmentioning
confidence: 98%
“…Several factors provide an exceptional opportunity to develop an integrated, context-specific service model in children’s homes and schools, including high expenditures in child welfare on clinical services (Brenner & Holzberg, 2000; Naylor et al, 2003), the pervasive nature of child welfare services, and recent attention on the poor conditions in foster care and children’s low academic achievement (Emerson & Lovitt, 2003; Zetlin & Weinberg, 2004). The results from our planning study also indicate that foster parents are interested in learning more effective ways to work with children with difficult behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…(3) Be an advocate to help children psychologically, emotionally, and academically (Emerson & Lovitt, 2003). (4) Don't hesitate to involve the foster family (Emerson & Lovitt, 2003;Noble Steyer, 1997). (5) Assist the foster family to help the child at home (Noble Steyer, 1997).…”
Section: Introductionmentioning
confidence: 98%
“…They struggle with personal, family, and educational challenges that other students do not confront (Altshuler, 1997;Courtney, 1999;George, Wulczyn, & Harden, 1999;Nowak-Fabrykowski, 2009;Nowak-Fabrykowski, Buchstein, & Helinski, 2007;Nowak-Fabrykowski & Piver, 2008). Many of them are not provided equitable educational opportunities for achievement nor stimulation to pursue further education (Emerson & Lovitt, 2003). Research has revealed the following strategies that can help foster children:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation